2019
DOI: 10.1038/s41598-019-52685-6
|View full text |Cite
|
Sign up to set email alerts
|

An aptasensor for the detection of Mycobacterium tuberculosis secreted immunogenic protein MPT64 in clinical samples towards tuberculosis detection

Abstract: This work presents experimental results on detection of Mycobacterium tuberculosis secreted protein MPT64 using an interdigitated electrode (IDE) which acts as a platform for capturing an immunogenic protein and an electrochemical impedance spectroscopy (EIS) as a detection technique. The assay involves a special receptor, single stranded DNA (ssDNA) aptamer, which specifically recognizes MPT64 protein. The ssDNA immobilization on IDE was based on a co-adsorbent immobilization at an optimized ratio of a 1/100 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 32 publications
(28 reference statements)
1
15
0
Order By: Relevance
“…Recently, limited studies have been published on the detection of Mycobacteri a using EIS‐based techniques. For examples, Sypabekova et al reported EIS‐based detection of M. tuberculosis secreted protein MPT64 using an interdigitated electrode [36]. The authors applied a special receptor, a single stranded DNA aptamer, which specifically recognizes MPT64 protein.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, limited studies have been published on the detection of Mycobacteri a using EIS‐based techniques. For examples, Sypabekova et al reported EIS‐based detection of M. tuberculosis secreted protein MPT64 using an interdigitated electrode [36]. The authors applied a special receptor, a single stranded DNA aptamer, which specifically recognizes MPT64 protein.…”
Section: Resultsmentioning
confidence: 99%
“…Most of the recent approaches use an aptamer element to engineer ligand-responsiveness and to regulate gene expression [23][24][25][26]44 . Aptamers are widely used, due to their high binding affinity against their respective target and their specificity [70][71][72][73][74][75][76][77][78][79][80][81][82] . In principal, the process of SELEX (Systematic Evolution of Ligands by Exponential enrichment) allows aptamer selection against any small molecule of interest 83,84 .…”
Section: Discussionmentioning
confidence: 99%
“…Sypabekova et al [18] presented results on the development of the aptasensor for the detection of MPT64, a Mycobacterium tuberculosis secreted protein, for tuberculosis (TB) diagnosis. This aptasensor used electrochemical impedance spectroscopy as determination method.…”
Section: Biomarker Detectionmentioning
confidence: 99%